Brain Stimulation Techniques in Research and Clinical Practice: A Comprehensive Review of Applications and Therapeutic Potential in Parkinson’s Disease - Ata Jahangir Moshayedi; Tahmineh Mokhtari; Mehran Emadi Andani (Brain Sciences)
Parkinson’s Disease (PD) is a progressive neurodegenerative disorder characterized by a range of motor and non-motor symptoms (NMSs) that significantly impact patients’ quality of life. This review aims to synthesize the current literature on the application of brain stimulation techniques, including non-invasive methods such as transcranial magnetic stimulation (TMS), transcranial electrical stimulation (tES), transcranial focused ultrasound stimulation (tFUS), and transcutaneous vagus nerve stimulation (tVNS), as well as invasive approaches like deep brain stimulation (DBS). We explore the efficacy and safety profiles of these techniques in alleviating both motor impairments, such as bradykinesia and rigidity, and non-motor symptoms, including cognitive decline, depression, and impulse control disorders. Current findings indicate that while non-invasive techniques present a favorable safety profile and are effective for milder symptoms, invasive methods like DBS provide significant relief for severe cases that are unresponsive to other treatments. Future research is needed to optimize stimulation parameters, establish robust clinical protocols, and expand the application of these technologies across various stages of PD. This review underscores the potential of brain stimulation as a vital therapeutic tool in managing PD, paving the way for enhanced treatment strategies and improved patient outcomes.